Perbedaan Tekanan Darah Sebelum dan Sesudah Terpapar Tekanan Panas (Studi pada Pekerja di Pabrik Tahu Bu Lis di Kec. Donorejo Kab. Pacitan tahun 2017) - Novi Nur Pratiwi; Winarko .; Narwati . (GEMA LINGKUNGAN KESEHATAN, 2018)
ne" A comfortable work environment, one of which can be seen from the physical factors in the working environment, especially in the aspect of the working climate (heat-pressure). The working climate (heat-pressure) in the workplace can affect the health of the workforce that will ultimately decrease productivity. According to the research results of Ari, Suwondo and coauthors in 2008, that the pressure the heat affect the workers blood pressure. Tofu factory belonging to the "Ibu Lis" is the manufacturer knew the only residing in Donorojo Subdistrict of Pacitan Regency. The results of measurements on a preliminary survey of the working climate in 3 point at the production of known average temperature 31,28 ºC. These results show has exceeded the threshold Value (NAB) based on the regulation of the Minister of Manpower and Transmigration Number PER 13/DOWNLOAD/X/2011 about the value of the thresholdfFactors are physical and chemical factors in the workplace amounted to 25.9 °C so that it can have an effect on the health of workers, in particular the blood pressure. In general, this research aims to know the difference in blood pressure before and after exposure to heat pressure on workers at Lady Lis’s tofu factory Donorojo Subdistrict of Pacitan Regency and in particular aiming to identify the characteristics of the workforce, the employment climate measure, measure the blood pressure of the workers before and after work, analyzing the difference of blood pressure before and after exposure to heat pressure, described the influence of characteristics of workers against blood pressure and climate control efforts work in the factory. This research includes the kind of observational studies and timebased data retrieval include cross sectional study. A large sample of 30 people taken in random, data is collected and processed and analyzed statistically (analytic) to test the hypothesis. The results showed there was a difference in blood pressure before and after exposure to heat pressure. Blood pressure changes also affected the characteristics of workers, among others, age, period of employment, and the habit of exercising. Factory owners are advised to install the ventilation is natural or manmade in the form vetilasi giving a fan or exhauster, workers should be more drinking lots of water, and take advantage of the break well. Key words : heat pressure, blood pressure, tofu factory